Cerebral autoregulation in hemorrhagic stroke: A systematic review and meta‐analysis of transcranial Doppler ultrasonography studies. Issue 1 (30th September 2018) - Minhas, Jatinder S.; Panerai, Ronney B.; Ghaly, George; Divall, Pip; Robinson, Thompson G.
Abstract: Purpose: International guidelines advocate intensive blood pressure (BP) lowering within 6 hours of acute intracerebral hemorrhage (ICH) to a target systolic BP of 130‐140 mm Hg, though more intensive lowering may be associated with adverse outcome. Observational studies suggest impaired cerebral autoregulation (CA) following ICH. Transcranial Doppler ultrasonography (TCD), alongside continuous BP monitoring, provides a noninvasive bedside investigation that offers detailed perspectives on physiological perturbations post‐acute ICH. This systematic review and meta‐analysis focuses on all TCD studies of CA in ICH. Methods: MEDLINE, EMBASE, and CENTRAL were searched for studies of hemorrhagic stroke and blood flow measurement. Results: Eight studies met inclusion criteria (293 ICH patients); CA was impaired up to 12‐days post‐acute ICH. Impaired CA was evidenced by reduced transfer function analysis phase and higher mean flow correlation values: these were associated with worsened clinical parameters including ICH‐volume and Glasgow Coma Scale. Meta‐analysis of CBV demonstrated that, compared to controls, mean CBV was significantly lower in the ipsilateral (49.7 vs 64.8 cm s −1, Z = 4.26, P < .0001) and contralateral hemispheres following ICH (51.5 vs 64.8 cm s −1, Z = 3.44, P = .0006). Conclusion: Lower mean CBV in combination with impaired CA may have implications for more intensive BP lowering and warrants further studies examining such strategies on cerebral blood flow and its regulatory mechanisms.